Yudicial Review of Teacher’s Certification Implementation in Magelang City - Mulyani, Sri; Prabowo, Wahyu (Proceeding International Conference on Science and Engineering, 2020)
This study aims to analyze the suitability between the implementation of primary school teacher certification policies with the laws and regulations in the city of Magelang. This study used a qualitative research method by conducting in-depth interviews, observation and documentation of research objects with data analysis techniques with interactive models proposed by Milles, Huberman and Saldana. The results of the analysis show that (1) Structural analysis shows that the implementation of the Teacher Certification Policy involves many organizations from the central government to regional governments with greater authority to the central government than regional governments, 2) Substance Analysis shows that the contents and material of the policy are not entirely applicable in the regions because there are variations in the conditions of schools and teachers in each district and city. Therefore, we need policies that specifically regulate the implementation of teacher certification policies in the regions. 3) Cultural analysis shows that there is no rejection of policy implementation due to the provision of professional allowances for teachers who have received an educator certificate. However, equity is needed in determining the quota of teachers receiving education certificates in order to meet the principles of justice and equity.